Hybrid Carbon Nanostructures for Direct Neuronal Interfacing - Peltola, Emilia (Frontiers in Materials, 2019)
We have developed a concept of hybrid carbon nanomaterials, where different allotropes of carbon are integrated into a structure. In order to facilitate the long-term measurements in vivo, the cellular response at the bioelectric interface should be optimized. Indeed, failure of implant integration has been proposed to be the main reason for sensor failure in vivo. Most strategies to enhance electrode integration into target tissue exploit a protective layer or barrier on an electrode substrate. For the detection of neurotransmitters, this is not as suitable strategy, because 1) such films give rise to an increased background electrode capacitance and impedance, and 2) act as a diffusion barrier and as a result, a decreased amount of the analyte reaches the electrode surface and the kinetics is compromised. Here we demonstrate that we can regulate the cellular response just with the electrode material. Specifically, we will show that it is possible to combine the properties of different carbon allotropes to obtain hybrid materials with enhanced neural response. We will present three examples of the approach: (i) functionalized nanodiamonds on tetrahedral amorphous carbon (ta-C) (ii) multi-walled carbon nanotubes grown directly on top of ta-C and (iii) carbon nanofibres synthesized on top of ta-C thin films. We demonstrate that hybrid structures may promote neural integration as, for example, hydrogen–terminated nanodiamonds enhance neural cell viability and while not increasing glial cell viability. Moreover, carbon nanofibers show prominence for tuning the cellular response as their dimension match biologically relevant cues. We show that nanofiber dimensions significantly alter glial and neural cell adhesion as well as their morphology. The properties of the hybrid structures can be tailored, both geometrically and chemically, with high definition. Consequently, these materials possess exceptionally high potential to achieve optimal host response just with the electrode material.